Comparing the effectiveness of therapeutic intervention based on healthy human theory with positive psychotherapy on self-compassion and cognitive fusion of mothers with autistic children - Amini , Mohammadreza; Torkan , Hajar; Yousefi , Zahra (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This research aims to compare the effectiveness of therapeutic intervention based on the healthy human theory with positive psychotherapy on self-compassion and cognitive fusion of mothers with children on the autism spectrum. Method: The research method was quasi-experimental (three groups-three stages) and the statistical population included all mothers of children with autism spectrum disorders who referred to autism centers in Isfahan city in July 2022, and 20 people were placed in each group in a targeted manner. The data in all three stages were collected by Neff's self-compassion questionnaire (2003) and Gillanders et al.'s (2014) cognitive fusion scale. Also, the positive psychotherapy package of Rashid and Seligman (2013) was implemented during 8 sessions of 90 minutes on the first experimental group and the therapeutic intervention package based on the healthy human theory was implemented as 9 sessions of 90 minutes on the second experimental group. Results: The results of variance analysis with repeated measurement showed that both therapeutic intervention packages based on healthy human theory and positive psychotherapy reduced cognitive fusion and increased self-compassion of mothers with children on the autism spectrum (p≥0.05) and this effectiveness in follow-up phase has also been stable. Also, the results of Bonferroni's post hoc test showed that there is no significant difference between the effectiveness of the two therapeutic intervention packages in any of the research variables. Conclusion: Based on the results of this research, psychologists can use both interventions to increase the awareness of mothers with children on the autism spectrum regarding the meaning and positive emotions in order to reduce cognitive fusion and increase self-compassion